Incidence of New-Onset Hypertension in Cancer Patients: A Retrospective Cohort Study. (16th December 2013) - Fraeman, Kathy H.; Nordstrom, Beth L.; Luo, Weixiu; Landis, Sarah H.; Shantakumar, Sumitra
Abstract : This retrospective cohort study was conducted to estimate incidence rates of new-onset hypertension in adult cancer patients identified from the Varian Medical Oncology outpatient database. Incidence rates of increasing levels of hypertension severity were calculated overall and for periods of chemotherapy exposure and nonexposure. Cox models sought predictors of new-onset hypertension severity among baseline and chemotherapy exposure variables. New-onset hypertension was observed in about one-third of 25, 090 patients with various cancer types. The incidence rates (IR) of severe and crisis-level hypertension, respectively, were the highest in patients with gastric (18.5 cases per 100 person-years (PY), 5.6 per 100 PY) and ovarian cancer (20.2 per 100 PY, 4.8 per 100 PY). The highest IR of moderate hypertension was observed in patients with renal cancer (46.7 per 100 PY). Across all cancers, chemotherapy exposure was associated with a 2–3.5-fold increase in risk of any degree of hypertension compared to periods of no chemotherapy; higher hypertension levels showed greater variability in relative risks by type and line of therapy but indicated an overall increase associated with chemotherapy exposure. These results help to elucidate the factors influencing HTN among cancer patients and the incidence of HTN relative to chemotherapy exposure.